Relegio-Paternalistic: Pengaruh Kepemimpinan Kiai Pesantren dalam Membangun Commitment Organisasi - Hariyanto, Hariyanto (Proceedings of Annual Conference for Muslim Scholars, 2019)
Islamic boarding school is one of the Islamic educational institutions. As a mode of Islamic education, there is educational process which involves various interrelated factors and supports the achievement of the objectives. It seems to be included as mentioned above for a long time and generally superficially understood. Therefore it is necessary to study, what is and how the essence of pesantren itself. Islamic boarding school is an Islamic education institution that recognized by society with a boarding system (campus) in which students receive religious education through a teaching system or madrasah. That is fully under the sovereignty of a leader or several Kyai with their charismatic characteristics. Kyai are often assumed to be a conservative, fanatical, puritanical and non-dialogical figure. However, it seems not all kyai have them. Even Kyai are the pioneers of renewal toward the concept of thought. They try to develop an education system in accordance with the demands of every era